Round Table - Scintigraphic diagnosis of abdominal tumors: coordinator Manlio Ferrari - Ferrari, Manlio (Cirugía del Uruguay, 1974)
The diagnosis of an abdominal mass includes 2 problems: to find out its origin in a specific viscus or tissue and to define its nature.